1988
DOI: 10.1021/bi00415a061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of serum transferrin at 3.3-.ANG. resolution

Abstract: Serum transferrin is a metal-binding glycoprotein, molecular weight ca. 80,000, whose primary function is the transport of iron in the plasma of vertebrates. The X-ray crystallographic structure of diferric rabbit serum transferrin has been determined to a resolution of 3.3 A. The molecule has a beta alpha structure of similar topology to human lactoferrin and is composed of two homologous lobes that each bind a single ferric ion. Each lobe is further divided into two dissimilar domains, and the iron-binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
262
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(271 citation statements)
references
References 52 publications
7
262
2
Order By: Relevance
“…The last co-ordination position of iron is occupied by a water molecule or a hydroxyl ion. Identical results have been obtained with rabbit serum transferrin and human lactoferrin [15,16]. Recent M6ssbauer studies have also confirmed the similarity between the two ironbinding sites in human transferrin [17].…”
Section: Transferrin and The Transferrin Receptorsupporting
confidence: 69%
“…The last co-ordination position of iron is occupied by a water molecule or a hydroxyl ion. Identical results have been obtained with rabbit serum transferrin and human lactoferrin [15,16]. Recent M6ssbauer studies have also confirmed the similarity between the two ironbinding sites in human transferrin [17].…”
Section: Transferrin and The Transferrin Receptorsupporting
confidence: 69%
“…The molecule shows a very high sequence identity to the sequence of rabbit serum Tf, whose structure has been solved by X-ray crystallography (Bailey et al, 1988). We are building a partial model of human Tf based on the rabbit structure, but it remains to be seen whether this will allow us to reconstruct the antibody/Tf complex structure.…”
Section: Discussionmentioning
confidence: 99%
“…The cleft is formed by two domains, N-I and N-II in the N-lobe and C-I and C-II in the Clobe. In human lactoferrin (hLF), human serum transferrin (hTF), rabbit serum transferrin (rTF) and chicken ovotransferrin (oTF), crystallographic data show that each ferric ion is directly coordinated to the side chains of two tyrosine residues, one histidine residue, one aspartic acid residue and two oxygens from the synergistic carbonate anion [3][4][5].…”
Section: Introductionmentioning
confidence: 99%